The spectacle of reconciliation: On (the) unsettling responsibilities to Indigenous peoples in the academy. (August 2019) - Daigle, Michelle
This paper places geographies of responsibility on stolen and occupied Indigenous lands in settler colonial Canada. Responsibilities to Indigenous lands and peoples are contextualized within the spectacle of reconciliation in Canada. In drawing on a range of critical analyses of reconciliation led by Indigenous scholars, I examine how the truth and reconciliation process has naturalized and fetishized Indigenous suffering and trauma while cultivating settler colonial spectacles whereby white settler Canadians engage in hollow performances of recognition and remorse. These spectacular spaces, I argue, become centered and severed from a larger terrain of settler colonial dispossession and violence that Indigenous peoples continue to resist on an everyday basis. I specifically focus on settler colonial spectacles and reconciliation mandates taking shape in Canadian postsecondary institutions. In doing so, I focus on how Canadian universities located on stolen Indigenous lands (actively supportive of the ongoing dispossession of Indigenous lands) continue to be a crucial site of settler colonial relations and a constitutive part of the settler colonial state.